STUDY GREEN LIQUID FERTILIZER PRODUCTION FROM HELIANTHUS A.L AND MUNTINGIA C.L PLANT - Caecillia Pujiastuti, Ketut Sumada (Jurnal Teknik Kimia, 2011)
Indonesia has many kinds of plants that can be utilized as an alternative raw materialliquid and solid fertilizer production. several types of plants that can be used as an alternative rawmaterial production of fertilizer is "Plants and Helianthus Muntingia CL A. L. Both types of plantson the leaves / twigs contain various types of ions such as ion Nitrogen (N), Phosphorous (P),Potassium (K), Magnesium (Mg) and calcium (Ca) so that this plant can be used as fertilizer. Inthis study, plant leaf composting process but do not do the extraction and fermentation processesthat run simultaneously. Solvent extraction process carried out with water, acid and sodiumphosphate hipophosphate with certain concentrations, whereas the process of fermentationwithout addition of microorganisms, known as "Self Fermentation".Extraction and fermentationprocess can accelerate the acquisition of fertilizers and facilitate the transport of ions inplants. The purpose of this study is to examine an alternative type of raw material production offertilizer, type and concentration of solvent, extraction time and fermentation, and leaf weightratio and the best solvent and the quality of manure produced. From the survey results revealedboth types of plants can be utilized as raw material for fertilizer, the best type of solvent with theconcentration of sodium hipophospahte 0.75%, extraction time and 50 days of fermentation andquality of the resulting liquid fertilizer for plants Plants Muntingia CL: ion N: 0 , 29%, PO4:0.37%, K: 0.55%, Mg: 0.11% and Ca: 0.025%, while for the plant Helianthus A. L ions N: 0.36%,PO4: 0.545%, K: 0.79%, Mg: 0.075% and Ca: 0.028% and on applications to rice plants knownto both types of green liquid fertilizer can increase the production of grain that is a liquidfertilizer Plants of Helianthus AL of 41.3% and Plants Muntingia CL by 29.9% compared with theuse of chemical fertilizers (urea, SP-36 and KCl), need for green manure liquid 1 liter per 100 m2of land.Key words: Muntingia CL, Helianthus AL, Fertilizer, Extraction and Fermentation.